2022
DOI: 10.33394/jk.v8i1.4659
|View full text |Cite
|
Sign up to set email alerts
|

Government Policy of Independent Learning-Independent Campus: Analysis of Student Knowledge and Readiness

Abstract: This study aimed to analyze the knowledge and readiness of students in the application of Independent Learning-Independent Campus (MBKM) in the Study Program of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
2
0
0
1
Order By: Relevance
“…Based on the results of the study, it was found that 89% of students knew that the study program had socialized the MBKM program, including the availability of MBKM policy documents such as regulations and guidelines that had been known mostly by students (87%). This is in line with the results of the research conducted by (Astro et al, 2022) saying that more students were aware of the MBKM policy as they got socialization from their university. In addition, Yuliasari (2022) in her study found that 64% of the students knew a lot about MBKM program from their lecturers.…”
Section: Figure 1 Students' Understanding Of Mbkmsupporting
confidence: 89%
“…Based on the results of the study, it was found that 89% of students knew that the study program had socialized the MBKM program, including the availability of MBKM policy documents such as regulations and guidelines that had been known mostly by students (87%). This is in line with the results of the research conducted by (Astro et al, 2022) saying that more students were aware of the MBKM policy as they got socialization from their university. In addition, Yuliasari (2022) in her study found that 64% of the students knew a lot about MBKM program from their lecturers.…”
Section: Figure 1 Students' Understanding Of Mbkmsupporting
confidence: 89%
“…Most (87%) have also been known to the students. It is consistent with the findings of Apoko's research Astro et al, 2022).…”
Section: Figure 1 the Students' Knowledge On The Policy Of Mbkm Programsupporting
confidence: 93%
“…Persoalan yang muncul adalah pengelolaan dan pengaturan kegiatan ekstrakurikuler belum dirumuskan dalam bentuk jadwal yang terstruktur sehingga menimbulkan polemik diantaranya rumusan materi, model pelaksanaan, pengelolaan, dan evaluasi. (Astro et al, 2022) Hal ini tentu membutuhkan kajian untuk membuat perencanaan, pedoman pelaksanan, dan lembar evaluasi kegiatan ekstrakurikuler keagamaan dengan mempertimbangkan indikator yang berlaku kemudian menuntaskan materi. (Vita Septia Pratami, 2019).…”
Section: Pendahuluanunclassified